Analysis of Household Waste Generation and Composition as a Basis for Evaluation of the Waste Management System in Bangunjiwo Village, Kasihan District, Bantul Regency - Hendry Edy; Limpat Wibowo Aji (SAINTEKS : Jurnal Sain dan Teknik, 2026)
The increase in household waste generation in rural areas is a serious challenge due to population growth and changes in consumption patterns. Bangunjiwo Village, Bantul Regency, as a semi-urban area, faces increasing waste pressure, while the management capacity based on the Reduce, Reuse, and Recycle Waste Processing Site (TPS 3R) is not yet fully commensurate with the actual generation load. This study aims to analyze the generation and composition of household waste and evaluate the suitability of the TPS 3R capacity as a basis for improving the rural waste management system. The study uses a quantitative descriptive approach with an evaluative perspective based on capacity ratio analysis and service levels. Secondary data were obtained from village waste management reports and the Bantul Regency Environmental Agency for the 2018–2024 period. The analysis includes calculating per capita waste generation, waste composition, TPS 3R processing capacity, and identifying the gap between actual generation and system service capacity. The results show that the composition of waste is dominated by organic fractions (57%), followed by plastic (23%), paper (12%), and metal and glass (8%). A capacity evaluation indicates that the 3R Waste Management Sites (TPS 3R) have not been able to keep up with the total daily waste generation, resulting in service gaps and unoptimally processed residues. This study offers an integrated evaluative approach that links the characteristics of waste generation and composition with the operational capacity of the 3R TPS as a framework for assessing rural waste management systems. These findings provide a basis for data-driven planning for capacity improvement and optimization of sorting systems, and can be replicated in villages with similar characteristics to support more effective and sustainable waste management.